2016
DOI: 10.1097/tp.0000000000001113
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Midodrine Use

Abstract: Background Midodrine is prescribed to prevent symptomatic hypotension and decrease complications associated with hypotension during dialysis. We hypothesized that midodrine use before kidney transplantation may be a novel marker for posttransplant risk. Methods We analyzed integrated national U.S. transplant registry, pharmacy records and Medicare claims data for 16,308 kidney transplant recipients transplanted 2006–2008, of whom 308 (1.9%) had filled midodrine prescriptions in the year prior to transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Interestingly, the RI during protocol biopsies correlates more with recipients’ factors (for example, age and central hemodynamic factors) than with graft or histologic factors 10 . Hypotension in the pre-transplant period might also be a risk factor for adverse outcomes in the post-transplant period, evidenced by recent studies associating the use of midodrine in the pre-transplant period with graft failure, death, and major adverse cardiovascular events (MACE) post-transplant 11, 12 .…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Interestingly, the RI during protocol biopsies correlates more with recipients’ factors (for example, age and central hemodynamic factors) than with graft or histologic factors 10 . Hypotension in the pre-transplant period might also be a risk factor for adverse outcomes in the post-transplant period, evidenced by recent studies associating the use of midodrine in the pre-transplant period with graft failure, death, and major adverse cardiovascular events (MACE) post-transplant 11, 12 .…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…In KT alone patients, end-stage renal disease largely develops from hypertension and diabetes, which lead to calcification and remodeling of large vessels and arterial stiffening resulting in decreased vascular compliance, myocardial fibrosis resulting in diastolic dysfunction, and autonomic dysfunction. 5 These physiologic changes tend to worsen with hemodialysis use and with more time awaiting organ transplantation. A patient with this underlying pathophysiology, who then develops hypotension with or without hemodialysis, represents a higher risk patient, as their hypotension is likely related to concomitant cardiovascular compromise.…”
Section: Discussionmentioning
confidence: 99%
“…The need for midodrine before kidney transplantation (KT) alone has been shown to increase the risk for poor posttransplant outcomes including delayed graft function, graft failure, and death. 5 , 6 As a result, in the kidney transplant program at our institution, the need for midodrine is a contraindication to listing for kidney transplant. However, specifically in cases of liver transplantation alone for HRS, pretransplant use of midodrine has not been associated with differences in renal function or mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown a higher risk of DGF among patients with pretransplant hypotension 5 and those taking midodrine, a commonly used medication for intradialytic hypotension. 6,7 Whether the association of DGF and blood pressure holds true across the range of blood pressure and whether this risk differs for certain high-risk donor and recipient phenotypes is unclear. Also, hypotension is likely a marker of high-risk recipient phenotype [8][9][10][11][12] and it is possible that blood pressure potentially mediates some of the DGF risk in high-risk recipients, but the extent of this contribution is not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying risk factors that may be potentially modifiable would allow for interventions to lower DGF incidence. Prior studies have shown a higher risk of DGF among patients with pre‐transplant hypotension 5 and those taking midodrine, a commonly used medication for intradialytic hypotension 6,7 . Whether the association of DGF and blood pressure holds true across the range of blood pressure and whether this risk differs for certain high‐risk donor and recipient phenotypes is unclear.…”
Section: Introductionmentioning
confidence: 99%